2017
DOI: 10.1371/journal.pone.0183543
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Ixodes ricinus by Borrelia burgdorferi sensu lato in peri-urban forests of France

Abstract: Lyme borreliosis is the most common tick-borne disease in the northern hemisphere. In Europe, it is transmitted by Ixodes ticks that carry bacteria belonging to the Borrelia burgdorferi sensu lato complex. The objective of this work was to explore eco-epidemiological factors of Lyme borreliosis in peri-urban forests of France (Sénart, Notre-Dame and Rambouillet). We investigated whether the introduction of Tamias sibiricus in Sénart could alter the density of infected ticks. Moreover, the density and tick infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 74 publications
1
27
1
Order By: Relevance
“…Contrasting results were observed [12] in three geographically distinct areas of eastern Romania where the estimated prevalence of eight Borrelia species was very similar between adults and nymphs. Similar results have been already confirmed for I. ricinus [61] over a three-year survey in a peri-urban forest in the south of Paris, France. Strnad et al [49] reported that the overall prevalence of B. burgdorferi (s.l.)…”
Section: Tick Stages: Larvae Vs Nymphs Vs Adultssupporting
confidence: 86%
“…Contrasting results were observed [12] in three geographically distinct areas of eastern Romania where the estimated prevalence of eight Borrelia species was very similar between adults and nymphs. Similar results have been already confirmed for I. ricinus [61] over a three-year survey in a peri-urban forest in the south of Paris, France. Strnad et al [49] reported that the overall prevalence of B. burgdorferi (s.l.)…”
Section: Tick Stages: Larvae Vs Nymphs Vs Adultssupporting
confidence: 86%
“…Several Borrelia burgdorferi ( s.l. ) genospecies ( B. lusitaniae , B. spielmanii and B. garinii ) were detected in ticks which was not surprising as they have already been identified in many European countries and particularly in the Senart Forest [7]. Interestingly, these species were only detected in questing females.…”
Section: Discussionmentioning
confidence: 87%
“…In addition to these general patterns, some unexpected data were observed, the most striking being no peak activity in spring 2017 (April and May) with tick densities very similar to those recorded in March. Abiotic factors such as temperature, relative humidity and rainfall, or fluctuating host numbers in the sampling area are known to influence questing tick abundance and activity patterns [2934] and could explain these unusual observations. It is important to note that 2017 was distinguished by an abnormally wet March, with total rainfall much higher than that recorded in previous years in the same area (71.3, compared to 11.2, 33.6 and 61.7 mm rain/month in 2014, 2015 and 2016, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Continued detection is consistent with the year-round presence of reservoir hosts in the sampling area (wood mice, bank voles, Siberian chipmunks, roe deer, common blackbird, European robin, song thrush, etc.) [34, 44, 45]. The continued presence of reservoir hosts could facilitate the circulation of dominant species, and maintain, even at low rates, less prevalent pathogen species that may not be detected by a single sampling.…”
Section: Discussionmentioning
confidence: 99%